AB0338 ELDERLY ONSET RHEUMATOID ARTHRITIS AND POLYMYALGIA RHEUMATICA: COMPARATIVE CLINICAL STUDY. (June 2019) - Martínez-Morillo, Melania; Prior-Español, águeda; Brandy-Garcia, Anahy; Pérez, Susana Holgado; Aparicio-Espinar, María; Gifre, Laia; Riveros-Frutos, Anne; Sangüesa-Gomez, Clara; Camins-Fàbregas, Jordi; Casafont-Solé, Ivette; Nack, Annika; Olive, Alejandro; et al.
Abstract : Background: Polyarthritis at the elderly people usually has a similar onset with an acute inflammatory character and scapular girdle involvement. Differentiating elderly onset rheumatoid arthritis (EORA) and polymyalgia rheumatica (PMR) can be a diagnostic challenge. Objectives: To analyse the clinical and analytical differences between EORA and PMR. Methods: Longitudinal observational study of patients older than 60 years newly diagnosed with EORA (ACR/EULAR 2010) and PMR (ACR/EULAR 2012). Inclusion: consecutive and voluntary. Follow-up time: 12 months. A single rheumatologist made all follow-up visits. The clinical-epidemiological and analytical characteristics were collected. The statistical study was performed with Stata 15.1. Results: 45 EORA were recruited (53% women; mean age 74.8 ± 7.5) and 20 PRM (85% women; mean age 76.6±5.0). 75% of EORA had scapular girdle involvement, but only 44% of the pelvic girdle. All had peripheral arthritis, and the small joints of the hands were involved in 93.3%, with edema in 46.7%. Forty percent of EORA patients were seropositive (RF> 20 IU/mL and/or ACPA> 20 U/mL): 33% RF positive (132.8 ± 126 IU/mL), 28.9% for ACPA (2 cases [15.4%] from 100 to 250 U/mL and 11 cases [84.6%] above 250 U/mL) and in 10 patients [22.2%] double positive). All patients with PMR patients had shoulder girdle involvement and 90% of the pelvic girdle. None of them had peripheral arthritis. RF was positive in one patient (73 IU/mL) and ACPA in 2 patients (titers between 20-40 U/mL). No patient was double positive. Table 1 and 2 . After 12 months of follow-up, there was no difference between the dose of glucocorticoids received in patients with EORA and PMR (p = 0.684). There were also no differences in glucocorticoids adverse effects according to the diagnosis (p = 0.734). Regarding the use of immunosuppressors, this was higher in patients with EORA (91% EORA and 20% PMR), according to the usual clinical practice guidelines. The percentage of remission in PMR at 12 months was 95%. However, using DAS 28-VSG, only 40.9% of patients with EORA were in remission at 12 months (p=0.003). Conclusion: The female predominance was higher in PMR than in EORA. The scapular girdle involvement, but especially the pelvic girdle, was more frequent in PMR. In contrast, involvement of peripheral joints and edema were more frequent in EORA. RF and ACPA were more frequent in EORA. There were no other analytical differences that would help their differential diagnosis. The mean and accumulated doses of glucocorticoids during the first 12 months were similar, as well as the percentage of side effects. Immunosuppressors are more frequently used in EORA than in PMR. Remission is achieved more commonly in PMR than in EORA. References: [1] Olivieri I, Pipitone N, D' Angelo S, Padula A, Salvarani C. Late-onset rheumatoid arthritis and late-onset spondyloarthritis. Clin Exp Rheumatol 2009;27(4 Suppl 55):S139-145. [2] Pease CT, Haugeberg G, Montague B, Hensor EMA, Bhakta BB, Thomson W, et al. Polymyalgia rheumatica can be distinguished from late onset rheumatoid arthritis at baseline: results of a 5-yr prospective study. Rheumatology 2009;48(2):123-7. Disclosure of Interests: None declared